The Hippo Pathway Effector Transcriptional Co-activator With PDZ-Binding Motif Correlates With Clinical Prognosis and Immune Infiltration in Colorectal Cancer - Wang, Yutong; Nie, Hui; Li, Huiling; Liao, Zhiming; Yang, Xuejie; He, Xiaoyun; Ma, Jian; Zhou, Jianhua; Ou, Chunlin (Frontiers in Medicine, 2022)
The transcriptional co-activator with PDZ-binding motif (TAZ) is a downstream effector of the Hippo pathway. It has been identified as an oncogene in certain tumor types; however, the function and role of TAZ in colorectal cancer (CRC) has not been illustrated. Here, we aimed to analyze the expression and role of TAZ in CRC. In this study, we investigated the expression level of TAZ in 127 CRC and matched adjacent normal tissues by immunohistochemistry (IHC) and analyzed its correlation with clinicopathological characteristics in CRC. Moreover, we further analyzed the role of TAZ in the CRC-associated immunology using integrative bioinformatic analyses. The cBioPortal and WebGestalt database were used to analyze the co-expressed genes and related pathways of TAZ in CRC by GO and KEGG enrichment analyses. Meanwhile, the correlations between TAZ and the infiltrating immune cells and gene markers were analyzed by TIMER database. Our study revealed that TAZ expression is higher in CRC tissues than in matched adjacent non-tumor tissues. In addition, CRC patients with higher TAZ expression demonstrated poor overall survival and recurrent-free survival rates as compared to CRC patients with lower expression of TAZ. Furthermore, the TAZ expression was identified to closely associate with the immune infiltration of CD4+ T, CD8+ T, and B cells. Taken together, our findings suggest that TAZ may serve as a promising prognostic biomarker and therapeutic target in CRC.